2017
DOI: 10.15171/ijb.1530
|View full text |Cite
|
Sign up to set email alerts
|

Biological Removal of the Mixed Pharmaceuticals: Diclofenac, Ibuprofen, and Sulfamethoxazole Using a Bacterial Consortium

Abstract: The presence of pharmaceuticals at low concentrations (ng to μg) in the environment has become a hot spot for researchers in the past decades due to the unknown environmental impact and the possible damages they might have to the plantae and fauna present in the aquatic systems, as well as to the other living organisms. The aim of the present investigation was to develop a bacterial consortium isolated from different origins to evaluate the ability of such a consortium to remove a mixture of pharmaceuticals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…This observation was confirmed in our former paper, in which the DCF was better removed by the D15 strain in the presence of glucose (82%) than in metabolic conditions (52%) [21]. The same findings were figured out in conjunction with two strains, D15 and D16, to eliminate a mixture of the drugs, where glucose accelerates drug mix elimination [30]. The results presented differed from the above as the elimination rate of DCF as the single source of carbon is higher than in the presence of a supplemental source of carbon (glucose).…”
Section: Resultssupporting
confidence: 77%
“…This observation was confirmed in our former paper, in which the DCF was better removed by the D15 strain in the presence of glucose (82%) than in metabolic conditions (52%) [21]. The same findings were figured out in conjunction with two strains, D15 and D16, to eliminate a mixture of the drugs, where glucose accelerates drug mix elimination [30]. The results presented differed from the above as the elimination rate of DCF as the single source of carbon is higher than in the presence of a supplemental source of carbon (glucose).…”
Section: Resultssupporting
confidence: 77%
“…Bioremediation is considered as a safe economical, efficient, and sustainable technology for restoring drug molecule-contaminated sites (Zhang et al 2013;Gavrilescu et al 2015). The bacterial classes of Gammaproteobacteria (Pseudomonas, Enterobacter, Stenotrophomonas, Lysobacter), Betaproteobacteria (Burkholderia, Delftia, Cupriavidus), Alphaproteobacteria (Sphingomonas), and Actinobacteria (Arthrobacter, Rhodococcus) are considered as highly active paracetamoldegrading microorganisms (Zhang et al 2013;Aissaoui et al 2017;Żur et al 2018a, b). It was further reported that some bacterial strains from the genus Pseudomonas could degrade pharmaceuticals including diclofenac, 4aminophenol, ibuprofen, and sulfamethoxazole (Wu et al 2012;Aissaoui et al 2017;Edrees et al 2017b;Żur et al 2018a, b).…”
Section: •−mentioning
confidence: 99%
“…The bacterial classes of Gammaproteobacteria (Pseudomonas, Enterobacter, Stenotrophomonas, Lysobacter), Betaproteobacteria (Burkholderia, Delftia, Cupriavidus), Alphaproteobacteria (Sphingomonas), and Actinobacteria (Arthrobacter, Rhodococcus) are considered as highly active paracetamoldegrading microorganisms (Zhang et al 2013;Aissaoui et al 2017;Żur et al 2018a, b). It was further reported that some bacterial strains from the genus Pseudomonas could degrade pharmaceuticals including diclofenac, 4aminophenol, ibuprofen, and sulfamethoxazole (Wu et al 2012;Aissaoui et al 2017;Edrees et al 2017b;Żur et al 2018a, b). A number of Pseudomonas strains able to remediate paracetamol present individually or in consortium in aqueous solutions have been reported in literature.…”
Section: •−mentioning
confidence: 99%
“…The number of pharmaceuticals discharged into the environment is an increasingly severe problem. More than 3500 pharmaceutical substances have been identified in surface water and treated wastewater, excluding metabolites and other transformation products (Aissaoui et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%